Positive and negative control of helicase recruitment at a bacterial chromosome origin - Winterhalter, Charles; Stevens, Daniel; Fenyk, Stepan; Pelliciari, Simone; Marchand, Elie; Cronin, Nora B; Soultanas, Panos; Costa, Tiago; Ilangovan, Aravindan; Heath, Murray (bioRxiv, 2021)
The mechanisms responsible for helicase loading during the initiation of chromosome replication in bacteria are unclear. Here we report both a positive and a negative mechanism for directing helicase recruitment in the model organism Bacillus subtilis. Systematic mutagenesis of the essential replication initiation gene dnaD and characterization of DnaD variants revealed protein interfaces required for interacting with the master initiator DnaA and with a specific single-stranded DNA (ssDNA) sequence located in the chromosome origin (DnaD Recognition Element, DRE). We propose that the location of the DRE within the replication origin orchestrates recruitment of helicase to achieve bidirectional DNA replication. We also report that the developmentally expressed repressor of DNA replication initiation, SirA, acts by blocking the interaction of DnaD with DnaA, thereby inhibiting helicase recruitment to the origin. These findings significantly advance our mechanistic understanding of helicase recruitment and regulation during bacterial DNA replication initiation. Because DnaD is essential for the viability of clinically relevant Gram-positive pathogens, DnaD is an attractive target for drug development. Competing Interest Statement The authors have declared no competing interest.